Job Design And Organizational Climate : Does Job Satisfaction Really Matter For Employee Performance? - Almadella; Widodo Sunaryo; Yayan Hadiyat (International Journal of Economics Accounting and Management, 2025)
This research aims to analyze the influence of Job Characteristics and Organizational Climate on Employe Performance thru Job Satisfaction as an intervening variable at PT XYZ in Bogor. The background of this research stems from the importance of strengthening job characteristics and a conducive organizational climate in improving employe satisfaction and performance in the manufacturing industry environment. The research method used is a quantitative approach with path analysis techniques. Data was collected by distributing questionnaires to 157 respondents who are employes at PT XYZ. The research results indicate that Job Characteristics and Organizational Climate have a positive and significant effect on Job Satisfaction. However, the effect of Job Satisfaction on Employe Performance is positive but not significant. Nevertheless, Job Characteristics and Organizational Climate still have a direct positive influence on Employe Performance. This finding indicates that improving job characteristics and creating a positive organizational climate can boost employe performance, although the effect thru job satisfaction is not yet maximized. The conclusion of this research is that strengthening Job Characteristics and Organizational Climate needs to be a primary focus in the strategy for improving employe performance at PT XYZ